2012
DOI: 10.1042/bj20110535
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glutaminyl cyclase attenuates cell migration modulated by monocyte chemoattractant proteins

Abstract: QC (glutaminyl cyclase) catalyses the formation of N-terminal pGlu (pyroglutamate) in peptides and proteins. pGlu formation in chemoattractants may participate in the regulation of macrophage activation and migration. However, a clear molecular mechanism for the regulation is lacking. The present study examines the role of QC-mediated pGlu formation on MCPs (monocyte chemoattractant proteins) in inflammation. We demonstrated in vitro the pGlu formation on MCPs by QC using MS. A potent QC inhibitor, PBD150, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…In contrast to DP4 and aminopeptidase P, the mature pE-modified N-terminus of CCL2 is not protected against MMP1 cleavage (McQuibban et al 2002, Cynis et al 2011. Furthermore, inhibition of QC activity by a competitive inhibitor or by RNAi suppressed monocytic cell migration (Cynis et al 2011, Chen et al 2012. Hence, the prevention of pE-formation has the potential to enhance chemokine degradation by suppression of N-terminal maturation and, thereby, opening alternative degradation pathway and this impairs the bioactivity of CCL2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to DP4 and aminopeptidase P, the mature pE-modified N-terminus of CCL2 is not protected against MMP1 cleavage (McQuibban et al 2002, Cynis et al 2011. Furthermore, inhibition of QC activity by a competitive inhibitor or by RNAi suppressed monocytic cell migration (Cynis et al 2011, Chen et al 2012. Hence, the prevention of pE-formation has the potential to enhance chemokine degradation by suppression of N-terminal maturation and, thereby, opening alternative degradation pathway and this impairs the bioactivity of CCL2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, others and we described that the pE protein modification is an important posttranslational step in CCL2 maturation (Cynis et al 2011, Chen et al 2012. Owing to the cyclization of the N-terminal CCL2 glutaminyl precursor into pE, the positive charge of the N-terminus is lost resulting in resistance against cleavage by aminopeptidases such as dipeptidyl peptidase 4/CD26, which is highly expressed in FTC and PTC (Kehlen et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, it is still unclear whether the cyclization reaction occurs post-translationally or co-translationally. Several papers reported that the conversion of glutaminyl peptides to their respective pyroglutamyl peptides can be accomplished by adding QC in vitro [24], [25]. However, a recent report described that pGlu formation likely occurs in the initial stage of protein folding in vivo , specifically before the formation of structured intermediates [26], thus supporting a co-translational cyclization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…And the pE-CCL2 levels in cerebrospinal fluid correlates with the faster cognitive decline in prodromal AD patients. Accordingly, inhibiting the generation of pE-CCL2 is believed to be a promising new approach for the prevention and treatment of neuroinflammation at the beginning of AD [9].…”
mentioning
confidence: 99%